Analisis Tingkat Pengetahuan Mahasiswa Program Studi Farmasi Terhadap Swamedikasi Obat Bebas dan Bebas Terbatas - Felisitas Feli; Liza Pratiwi; Shoma Rizkifani (State University of Gorontalo, 2022)
Over-the-counter and over-the-counter drugs are the two classes of drugs commonly used for self-medication. The high risk caused by irrational use of drugs must be considered by each individual in order to increase knowledge and good behavior in self-medication. This study aims to analyze the level of knowledge and behavior level of the students of the Pharmacy Study Program, Tanjungpura University and analyze the relationship between the semester level and the two variables. This research method uses the Spearman rank correlation test with the SPSS Version 26 application in the bivariate analysis test with a cross-sectional approach. Respondents used as many as 232 people with the method of taking Statified Random Sampling. The results showed that the majority of respondents were female, aged 17-22 years, and mostly used paracetamol purchased at pharmacies without a doctor's prescription to treat fever. Respondents have a level of knowledge that falls into the category of less (40.5%) with appropriate self-medication behavior (97.4%). The variable level of knowledge and level of behavior has a significant relationship (p-value = 0.006). The semester level variable and the level of knowledge have a significant relationship (p-value = 0.000). Semester level and behavioral level variables have a significant relationship (p-value = 0.026). The conclusion is that there is a relationship between the semester level and the level of knowledge and behavior of the students of the Pharmacy Study Program at Tanjungpura University towards the use of over-the-counter and over-the-counter drugs in self-medication.